Studi Literatur: Penerapan Persoalan Transportasi dalam Biaya Pengangkutan Barang di Pabrik-Pabrik yang Ada di Indonesia - Icha Amelia; Fakhrezi, Ilham Achmad; Marshanda Suraya; Siti Salamah Br. Ginting (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study examines the application of transportation problems in an effort to minimize goods transportation costs in various factories in Indonesia, using a Systematic Literature Review (SLR) approach. Transportation problems, as a part of operations research, focus on optimizing distribution costs from sources to destinations. In the industrial context, good planning and strategy are essential to save transportation costs and increase profits. This study analyzes ten relevant journals published between 2017 and 2025, exploring various methods such as the transportation model, North West Corner, Stepping Stone, and Vogel's Approximation Method (VAM), including its modification (MVAM), to achieve efficiency in logistics distribution. The results of the study indicate that the application of these methods significantly contributes to reducing operational costs, accelerating distribution processes, and increasing overall logistics effectiveness in the Indonesian manufacturing sector.